2021
DOI: 10.35848/1882-0786/abf319
|View full text |Cite
|
Sign up to set email alerts
|

Infiltration of water vapor into multi-layer ceramic capacitors under highly accelerated temperature and humidity stress tests

Abstract: Although it has been suggested that infiltration of water vapor into multi-layer ceramic capacitors (MLCCs) can increase leakage current, few studies have reported how this increase is directly linked to the infiltration. In this work we performed accelerated temperature and humidity stress tests with heavy water as a tracer and investigated, using secondary ion mass spectrometry, whether traces of water vapor could be detected in MLCCs. In particular, deuterium was found in areas where an augmented leakage cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In previous studies, it was presumed that when water vapor infiltrated the interface between the anode-side inner electrode and the dielectric, electrolysis occurred at the interface, as shown in the equation below, and D + was attracted to the cathode-side inner electrode by migration through the dielectric. [23][24][25] Considering the results of Fig. 3(a) and the aforementioned presumption, the deuterium in the dielectric is presumed to exist as D +…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In previous studies, it was presumed that when water vapor infiltrated the interface between the anode-side inner electrode and the dielectric, electrolysis occurred at the interface, as shown in the equation below, and D + was attracted to the cathode-side inner electrode by migration through the dielectric. [23][24][25] Considering the results of Fig. 3(a) and the aforementioned presumption, the deuterium in the dielectric is presumed to exist as D +…”
mentioning
confidence: 94%
“…Consequently, the leakage current increases as the protons diffuse into the dielectric. 23) It was verified that water vapor infiltrates the MLCC 24) using deuterium, as a tracer. It was observed, that deuterium was biased toward the cathode-side inner electrode in the BaTiO 3 -based dielectric exhibiting increased leakage current.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The protons then diffuse into the dielectrics, thereby increasing the leakage current. 23,24) Numerous researchers have studied the relationship between perovskites and hydrogen. Waser et al reported the solubility and diffusion of hydrogen defects in perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…30) Using secondary ion mass spectroscopy (SIMS) analyses and complex impedance measurements, Morito et al confirmed that protons dissolved the interstitial hydrogen impurity in (Ba, Sr)TiO 3 thin films annealed at 400 °C. 31) Although we previously clarified vapor infiltration into an MLCC in a HAST, 24) hydrogen infiltration into BaTiO 3 -based dielectrics between the internal electrodes in the active layer of the MLCC has not been clarified, and the cause of the increase in the leakage current is debatable.…”
Section: Introductionmentioning
confidence: 99%